1977
DOI: 10.1038/ki.1977.8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic progressive renal disease: Rate of change of serum creatinine concentration

Abstract: The rate of change of the serum creatinine concentrations in 63 patients with chronic progressive renal disease of varied etiology was examined by linear regression analysis using the logarithm or the reciprocal of the serum creatinine concentration versus time. A single straight line was described by one or the other of these relationships in 53 patients. Six patients had an accelerated rate of nephron destruction terminally (two slopes) regardless of the mathematical analysis. The remaining four patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(55 citation statements)
references
References 18 publications
2
52
1
Order By: Relevance
“…In previous studies in smaller numbers of participants, a linear rate of decline has been reported (23)(24)(25)(26). In this large cohort, we found that as renal function declined, the rate of decline of renal function accelerated.…”
Section: Discussionsupporting
confidence: 55%
“…In previous studies in smaller numbers of participants, a linear rate of decline has been reported (23)(24)(25)(26). In this large cohort, we found that as renal function declined, the rate of decline of renal function accelerated.…”
Section: Discussionsupporting
confidence: 55%
“…In the series of Rutherford and colleagues (1977), rates varied as follows : glomerulonephritis 0.007-0.026, diabetes 0.003-0.038, polycystic kidneys 0.0015-0 .063, and pyelonephritis 0.000-0.014. The study (Rutherford et al 1977) also showed great variation from time to time in individual patients, with variations of over 10-fold.…”
Section: Nature Of the Underlying Diseasementioning
confidence: 99%
“…Many of these limitations are reduced when using serial observations in a given patient, but on occasions can have a profound influence on the relationships between plasma creatinine, creatinine clearance and renal function, vitiating attempts to plot or predict a steady course. Rutherford et al (1977) studied the course in 63 patients with diverse causes of renal failure. Although most patients seemed to pursue a steady course, with a single straight line relationship between 1/Cr and time, almost 20% of patients did not, and required the construction of 2 or more lines, implying an alteration in the slope at some point in their course.…”
Section: Mathematical Models Of Progression Of Renal Failurementioning
confidence: 99%
“…The attempt to repair damage begins with the recruitment of inflammatory cells but ends with an unchecked inflammatory response that activates matrixproducing cells leading to tubular cell apoptosis, irreversible scarring, loss of renal function, and ultimately ESRD [57] . The extent of damage rather than the underlying disease determines the outcome [58] . Progressive fibrosis is likely responsible for the disruption of glomerular and tubular architecture.…”
Section: Pathogenesismentioning
confidence: 99%